The Summer King - Melling, O. R. (Amulet Books, 2006)
Seventeen-year-old Laurel returns to her grandparents' home in Ireland, where she encounters "the roly-poly man," a cluricaun who sets Laurel on a quest to free her twin sister, thought to be dead, to live with her lover in the legendary world of Faerie.